Occurrences and Characteristics of Gold Mineralization in Rampi Block Prospect, North Luwu Regency, South Sulawesi Province, Indonesia - Arifudin Idrus; Suaib Mansur; Ahmad Ahmad; Rahmayuddin Rahmayuddin; Abdul Abdul (Geological Engineering Department Universitas Gadjah Mada, 2016)
This study is aimed to identify the occurences, characterisatics and genetic type of gold mineralization, and to elucidate the preliminary gold potential in the study area. Research method includes field observation of prospect geology, hydrothermal alteration and ore mineralization. Laboratory analysis consists of petrography, ore microscopy and ore chemistry. Geologically, quartz ± gold veins were found in Rampi block prospect, which are mainly hosted by metamorphic and metasediment rocks. The quartz veins has structurally segmented with massive, brecciated and laminated textures. Orientation and distribution of veins is controlled by NW–SE and NE–SW trending structures. Sulfides are present with minor abundance (<1 %). Pyrite is obviously observed and partially oxidized. Arsenopyrite and stibnite are minor, while basemetal (Pb, Zn) sulfides are very rare. Gold mineralization occurred in quartz veins and closely related to silica-clay and silicic alteration. Gold grade varies from 0.1 to 11 ppm Au (29 samples). Quartz veins contained high gold grade (>9 ppm) commonly show laminated and brecciated texture and has been undergone a supergene enrichment. According to several characteristics above, gold deposit in Rampi block prospect tends to meet the criteria of orogenic/mesothermal gold type (cf. Groves et al., 2003). The deposit shares similarities with Awak Mas prospect, which is already confirmed to be a mesothermal type in Luwu district (cf. Querubin and Walters, 2011). Therefore, discoveries of economic mesothermal gold deposits are still open in the metamorphic terrains, and thus, it requires a systematic exploration based on the genetic model of the deposit.